Internalization of the Value of Tawheed in the Communicative Interaction of Digital Da'wah Gus Baha' - Imam Safi'i; Sonia Isnaini Nabila; Firgi Nurdiansyah (Communicator: Journal of Communication, 2025)
This study examines the internalization of tauhid (Islamic monotheism) values in digital da'wah through a communicative interaction perspective, focusing on the sermons of Ahmad Bahauddin Nursalim on YouTube. The rapid expansion of digital media has transformed religious communication, enabling wider dissemination while simultaneously raising concerns about fragmented and superficial religious understanding. This research aims to analyze how tauhid is constructed, communicated, and internalized within the dynamics of digital interaction. Using a qualitative approach with digital content analysis, this study examines 15 selected video sermons published between 2022 and 2025. Data were collected through documentation and transcription, and analyzed using thematic coding, including open, axial, and selective coding. The findings reveal that tauhid is constructed not merely as an abstract theological doctrine but as a contextual and experiential framework integrated into everyday life. Communicatively, the internalization process is supported by narrative, dialogical, and reflective strategies, including metaphors, analogies, and rhetorical questions, which enhance both cognitive and affective engagement. Furthermore, YouTube's interactive and asynchronous features facilitate repeated exposure and collective interpretation through audience comments, thereby transforming da'wah into a participatory process of meaning-making. The study argues that effective digital da'wah requires integrating theological depth with contextual communication strategies. This research contributes to the development of Islamic communication studies by bridging theological and communicative dimensions within the framework of symbolic interactionism and mediatization. Practically, it offers insights for designing digital da'wah that fosters deeper, reflective, and sustainable internalization of religious values in contemporary Muslim societies.